The Effect of Service Quality, Utilization of Information Technology, and Innovation on Marketing Performance of Savings and Loan Cooperative Putra Mandiri Surabaya - Vincent Audi Santoso; Sengguruh Nilowardono (LPPM NAROTAMA UNIVERSITY, Indonesia, 2018)
This study aims to analyze the effect of service quality, utilization of information technology, and innovation on the marketing performance of Putra Mandiri Surabaya Savings and Loan Cooperatives partially and simultaneously. In this study the authors used accidental sampling techniques, where anyone who accidentally met with the researcher could be used as a sample. In this study, the number of samples the authors took as many as 130 people including members and prospective members of the cooperative. Data collection techniques used are using questionnaires and interviews. In calculating scoring, researchers used a Likert scale. The data analysis method used is multiple linear regression analysis. The results of this study indicate that the variables of Service Quality, Use of Information Technology, and Innovation have a significant effect on Cooperative Marketing Performance partially. Service Quality Variables, Information Technology Utilization, and Innovation have a significant effect on Cooperative Marketing Performance simultaneously.